2022
DOI: 10.3389/fgene.2022.949110
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a novel cellular senescence-related prognostic signature for predicting the survival and immune landscape in hepatocellular carcinoma

Abstract: Background: Cellular senescence is a typical irreversible form of life stagnation, and recent studies have suggested that long non-coding ribonucleic acids (lncRNA) regulate the occurrence and development of various tumors. In the present study, we attempted to construct a novel signature for predicting the survival of patients with hepatocellular carcinoma (HCC) and the associated immune landscape based on senescence-related (sr) lncRNAs.Method: Expression profiles of srlncRNAs in 424 patients with HCC were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…AC026412.3 is differentially expressed between HCC and normal tissues and has been linked to poor prognosis of HCC patients. [43,44] There has not yet been any research on AL445309.1, AL132639.2, AC116049.1, and AC009486.2; however, our study might assist in understanding the potential functions of these 4 lncRNAs.…”
Section: Discussionmentioning
confidence: 95%
“…AC026412.3 is differentially expressed between HCC and normal tissues and has been linked to poor prognosis of HCC patients. [43,44] There has not yet been any research on AL445309.1, AL132639.2, AC116049.1, and AC009486.2; however, our study might assist in understanding the potential functions of these 4 lncRNAs.…”
Section: Discussionmentioning
confidence: 95%
“…We found that the four cuproptosis-related lncRNAs that were modeled were all up-regulated in the high-risk group. Through high-throughput bioinformatics analysis, many studies have shown that AL031985.3 is associated with the prognosis of HCC and can be used to build a predictive model for the prognosis of HCC [42][43][44]. Previous studies have found that SNHG18 is abnormally expressed in glioma tissue specimens, and high expression of SNHG18 in gliomas enhances their radiation resistance [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of this expression may inhibit the proliferation and migration ability of hepatocellular carcinoma cells by regulating miR-193b-5p, which, in turn, affects ubiquitin specific peptidase 10 (USP10) [18]. Compared with LO2, AC026412.3 was also highly expressed in a variety of hepatocellular carcinoma cells (Hepg2, Huh7, and Hep3B), which may be associated with poor prognosis in hepatocellular carcinoma patients [19]. Elevated MKLN1-AS has been demonstrated to be one of the causes of poor prognosis in hepatocellular carcinoma patients, which is also consistent with our findings [20].…”
Section: Discussionmentioning
confidence: 99%